Teacher Agency in the Pedagogical Uses of ICT: A Holistic Perspective Emanating from Reflexive Practice - Ángela Novoa-Echaurren (MDPI AG, 2024)
This article discusses a case study on teacher agency about the pedagogical uses of information and communication technologies (ICTs). The investigation explored a school ecosystem that has developed a model of reflexive practice aimed at promoting teacher agency from a holistic and relational perspective. The primary case comprised six sub-cases using ICTs with students and deliberated on these uses by applying the reflexive model promoted within the school boundaries. Data were analyzed thematically. Observations of teaching practices with ICTs, reflexive practice sessions on ICT uses, and interviews with the heads of departments of the observed teachers yielded the relevance of collaborative agency in the context of the digital age as it brings together policy, theory, and practice. In line with the claims of relevant literature, the study shows that an articulated dialogue between these dimensions is relevant for using technologies in education according to the specificities of teachers' institutional ecosystem.